Visit Patterns of Human Immunodeficiency Virus Patients at Referral Health Facilities - Zain, Paisal; Arifin, Aya Yuriestia; Hansur, Lismayana; Sjatha, Fithriyah (Jurnal Jaminan Kesehatan Nasional, 2025)
Human Immunodeficiency Virus (HIV) infection remains a health problem in Indonesia, with cases increasing annually. HIV care services in Indonesia involve Primary Health Facilities (PHF) and Referral Health Facilities (RHF). This study aims to identify patterns of HIV patient visits to RHF. This cross-sectional study used secondary data from the National Health Insurance (NHI) for 2015–2023. HIV patients were identified based on ICD-10 diagnosis codes (B20–B24), with referral status as the independent variable. Analysis was performed using chi-square tests, and visit patterns were visualized using Sankey diagrams. Of the more than one million patients, 2,532 were identified as having HIV, resulting in more than 38,000 visits. Most patients were referred from community health centers to general hospitals, primarily for outpatient care. Age was significantly associated with referral status, while other demographic factors showed no association. Overall, the referral system is functioning effectively, but strengthening service capacity in PHF remains crucial to reduce the referral burden on hospitals.